3q29 microduplication syndrome: New evidence for the refinement of the critical region. Issue 4 (24th January 2023) - Bauleo, Alessia; Pace, Vincenza; Montesanto, Alberto; De Stefano, Laura; Brando, Rossella; Puntorieri, Domenica; Cento, Luca; Genuardi, Maurizio; Falcone, Elena
Abstract: Background: The 3q29 microduplication syndrome is a rare genomic disorder characterized by an extremely variable neurodevelopmental phenotype usually involving a genomic region ranging from 1.6 to 1.76 Mb. A small microduplication of 448.8 Kb containing only two genes was recently described in a patient with a 3q29 microduplication that was proposed as the minimal critical region of overlap of this syndrome. Methods: Molecular karyotyping (array‐CGH) was performed on DNA extracted from peripheral blood samples using Agilent‐California USA Human Genome CGH Microarray 4 × 180 K. The proband and his younger brother were further tested with a next generation sequencing (NGS) panel including genes implicated in autism spectrum disorder and in neurodevelopmental disorders. Quantitative real‐time PCR was applied to verify the abnormal array‐CGH findings. Results: Here, we report on a family with two males with neurodevelopmental disorders and an unaffected sibling with a small 3q29 microduplication (432.8 Kb) inherited from an unaffected mother that involves only two genes: DGL1 and BDH1 . The proband had an additional intragenic duplication inherited from the unaffected father. Further testing was negative for Fragile X syndrome and for genes implicated in autism spectrum disorder and in neurodevelopmental disorders. Conclusion: To the best of our knowledge, one of the family members here analyzed is the second reported case of a patient carrying a small 3q29 microduplication including only DGL1 and BDH1 genes and without any additional genetic aberration. The recognition of the clinical spectrum in patients with the critical region of overlap associated with the 3q29 duplication syndrome should prove valuable for predicting outcomes and providing more informed genetic counseling to patients with duplications in this region. Abstract : Pedigree for the family analysed in this study including the identified 3q29 microduplication variant.